THE IMPLEMENTATION OF PROBLEM BASED LEARNING (PBL) MODEL USING MULTIMEDIA IN IMPROVING NATURAL SCIENCE LEARNING ABOUT ENERGY FOR THE FOURTH GRADE STUDENTS - Wibowo, Ades Edi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Implementation of Problem Based Learning (PBL) Model Using Multimedia in Improving Natural Science Learning About Energy for The Fourth Grade Students. The purpose of this studys to describe and improve natural science learning about energy fourth grade students in the elementary school, and find barriers and solutions in the Implementationof using PBL models with multimedia. This study is a collaborative action research conducted in three cycles. Each cycle consists of two meetings of planning, implementation, observation, and reflection. The subjects of the study is the fourth grade students. The data comes from fourth grade students, fourth grade teacher, observer and documents.The validity of the data using triangulation of data and data sources. Learning has increased from cycle I to cycle III. The conclusions of this research is the application of PBL with the type of multimedia can enhance science teaching about energy fourth grade students.Keywords: Problem Based Learning (PBL), Multimedia, natural Science